ADAPT OR DIE: MISIOLOGI DI ERA 5.0 - Heldi Efraim Amung; Hendrik A. E. Lao (Ra'ah: Journal of Pastoral Counseling, 2025)
This article examines the transformation of missiology in the 5.0 era, employing a literature review method to analyze the impact of technological advancements and social changes on evangelization. The research findings highlight the need for innovative and digitally relevant evangelization strategies, as well as the importance of individual spiritual integrity in fulfilling the mission. Challenges such as materialism, cyberbullying, and easy access to adult content are discussed as obstacles, emphasizing the need for a contextual and comprehensive approach to spreading the Gospel in this era.